Challenges And Prospects Of Utilising Natural Resources Of Nepal For Sustainable Development Which Is Vacuum Or Zero - Khadka, Bhes Bahadur; Prasad, Jitender (A Bi-annual South Asian Journal of Research & Innovation, 2023)
This research article examines a sociological study of utilising natural resources of Nepal for sustainable development which is changeable every moment every second. This is role of sociology. Sociology is one of the vacuumed space or zero... Sociology component of social phenomena. Wideranch. Sociology start and development male, female from the Social activities. Sociology start from zero level and end of zero. That is the social process. Sociology is for example like a cloth rack. Kiwi fruit farming protection of natural resources which is contributing in national economy and Agro-forestry one of the Natural resources. Which is environment protection, soil erosion control, land slide control, economic support and sustainable land management. The research area is mostly use to slop and barer land in the mid-hill areas of Nepal. In This area is suitable for growing high-value kiwi fruit. That enhances biodiversity and uplifts communities by serving as a valuable source of income through agroforestry practices.